2012
DOI: 10.1007/s00402-012-1619-z
|View full text |Cite
|
Sign up to set email alerts
|

The use of enhanced recovery after surgery (ERAS) principles in Scottish orthopaedic units—an implementation and follow-up at 1 year, 2010–2011: a report from the Musculoskeletal Audit, Scotland

Abstract: A clinically guided and nationally supported process has proven highly successful in achieving a further uptake of enhanced recovery principles after lower limb arthroplasty in Scotland, which has resulted in clinical benefits to patients and reduced length of hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 22 publications
3
56
0
3
Order By: Relevance
“…[11][12][13][14][15][16][17][18][19][20][21] These previous studies certified that FT programs could decrease postoperative complications, postoperative length of stay (LoS), hospitalization costs, and improve patient satisfaction. [4][5][6][11][12][13][14][15][16][17][18][19][20][21] A good deal of publications has inspected the feasibility of FT programs for hepatic surgery, but the potency of these studies has not been discussed profoundly. As a consequence, we performed this meta-analysis for the sake of assessing the effects of implementation of FT programs on surgical outcomes compared with the traditional treatment plans following liver surgery.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20][21] These previous studies certified that FT programs could decrease postoperative complications, postoperative length of stay (LoS), hospitalization costs, and improve patient satisfaction. [4][5][6][11][12][13][14][15][16][17][18][19][20][21] A good deal of publications has inspected the feasibility of FT programs for hepatic surgery, but the potency of these studies has not been discussed profoundly. As a consequence, we performed this meta-analysis for the sake of assessing the effects of implementation of FT programs on surgical outcomes compared with the traditional treatment plans following liver surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, FT programs have been used in vascular surgery [5], breast surgery [6], urologic [7], and orthopedic surgery [8]. However, FT for liver surgery was first described in 2008 [9].…”
Section: Introductionmentioning
confidence: 99%
“…This approach often requires more dollars to be spent on some services in order to reduce the need for others. Studies have shown that optimized care pathways are associated with decreased postoperative lengths of stay, lower blood transfusion rates, and earlier mobilization 53,54 .…”
Section: Costsmentioning
confidence: 99%